The Fear: A Study of Consternation in Bradburry “The Night” - Asyida’, Miqda Al Auza’i Ashfahany; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (LPPM Universitas Bina Sarana Informatika, 2025)
This study examines themes of fear in Ray Bradbury’s The Night (1946) through the experience of the main character, Shorts. Using Fisher’s theory, this study focuses into how the environmental factors and self-control regulate human emotion, especially fear. A qualitative method is applied to explore the narrative, and reveals how external elements, such as the environment and others' reactions, as well as internal elements like past events and inner thoughts, influence Shorts's fear. The findings highlight how those factors give their impact to trigger human behavior, emphasizing the complicated connection between external circumstances and internal psychological states. Through Shorts's narrative, the study underscores the dynamic interaction between the external world and human emotion.